Alat Bukti Elektronik Menurut Hukum Acara Perdata dan Hukum Islam - Achmad Hasan Basri (Indonesian Journal of Islamic Law, 2019)
Abstrack: Modern technology, such as computers and mobile phones, has been widely utilized for its practicality as a tool to help facilitate people to do trade transaction for example. Furthermore, in this digital age, a myriad of virtual transactions have made use of electronic media which enables each party to get involved in the limitless and borderless business. For their security purposes, people use social media to keep their transaction in their account as evidence that they have carried out such online trading to anticipate any breach of contract and other legal issues. Electronic documents are included as legal evidence according to Law No. 11/2008 on information and electronic transactions, thus, it is necessary to analyze them regarding the use of electronic documents as evidence in Indonesian civil law, to find out what criteria that can be referred to make electronic documents as evidence in civil law, and to figure out the position of electronic documents as evidence in civil law reform in Indonesia. The present study is a normative juridical research method that refers to the legal norms and regulations as well as the court decisions and the living norms that develop in society. The research revealed that the use of electronic media can become evidence yet it cannot be used as stand-alone evidence. It must be determined by various components in it such as the need for expert witnesses and the interpretation of judges. Therefore, the present research expects to contribute theoretically in the field of law through which the use of electronic media will be no longer a legal problem and can continue to be used as evidence by the public.